Caring for the future: decrease in infant mortality in Maranhão State - Cristina Douat Loyola; Rosane Mara Pontes de Oliveira; Virginia Faria Damásio Dutra
ABSTRACT Objective: To report on the experience and care provided by the "Caring for the future" program to decrease infant mortality in 17 municipalities of Maranhão, in a proposal work of the Secretariat of Basic Care, in partnership with the Non-Governmental Organization called Centro Popular de Cultura e Desenvolvimento (Popular Center for Culture and Development/PCCD) from 2009 to 2015. Method: Experience Report of community care that made it possible to create and strengthen solidary relationships among community members. Results: The program decreased infant mortality rate and created in the supported communities a platform of health support, uniting information and care in Primary Care. The program trained 34 "Guardian Angels" and 170 "Supportive Caregivers", mapped seven thousand "luminous spots" and trained more than 7,000 caregivers in health. It served 17 municipalities, 27,191 pregnant women, 291,266 families. Final considerations: The program was a catalyst for actions: it unveiled hidden resources in the community, awakened collective responsibility, offered training and built solidary relationships.